The Emergence of AI-Driven Virtual Hospitals: Redefining Patient Care Beyond Physical Boundaries - Ifrah Hameed; Hafiz Muhammad Haseeb Khaliq (Pakistan Journal of Medicine and Dentistry)
Artificial intelligence (AI) has been introduced in a transformational era where AI-driven virtual hospitals have led healthcare departments. When combined with advanced AI technologies, telemedicine, and remote monitoring, these transformational platforms deliver comprehensive medical services, effectively surpassing physical boundaries. This development is revolutionizing patient care patterns by increasing accessibility and diagnostic precision as well as by enabling continuous monitoring and customized plans for treatment.